The governance of a university from an Islamic perspective - Che Omar, Azman (Universiti Teknologi MARA, Kelantan, 2018)
The successful operation of an organization and its sustainability are always measured by the execution of its winning strategies and least factored or caused by the effective management of the CEO and the top managers of the business organization or company. Their acumen in management were rarely discussed in many business management journals. The fact is that the top global companies are managed by the visionary CEOs had made them going up in the list of Fortune top 500. The university as an organization or company also being operated likes the business organization. If any company wants to survive in today’s volatile environment, it needs to make good profit. If no profit, then the company needs to struggle a lot in order to be operating. The company then must create or develop many strategies that are better than its competitors. Universities, like other organizations were established and operated to achieve their purposes. In Malaysia, they are two kinds of universities, namely private universities and public universities. Even though their outcomes are almost the same, that is the employability of their graduates, however, the purposes of their existence are not the same. The purpose of this paper is to develop a framework of good governance from the Islamic perspective of an university for attaining the academic excellence. The review of the paper is based through the Islamization of knowledge, that is the Islamization of the governance of an organization and not through the Islamic governance view. The outcomes or the results from the framework would become guidelines for any Muslim manager or an Islamic organization that enhancing more of their Islamic image.